Combined effects of boron, sodium and strontium on grain refinement of sterling silver grade 950 - Sakultanchareonchai S. (2014)
Combined effects of B, Na and Sr on grain refinement of sterling silver grade 950 were investigated. The silver alloys with different composition of B, Na and Sr were prepared in three steps including pre-alloy preparation, master alloy preparation and finally sterling silver casting. Characterization was performed by inductively coupled plasma - optical emission spectroscopy for determining chemical composition, and light microscopy, scanning electron microscopy and electron probe microanalysis for investigating microstructure. The tensile properties of the alloys were determined following the ASTM E 8M-96. The results revealed that micro-scale addition of B, Na and Sr plays a significant role in grain refinement. Effective grain refinement with bright surface appearance, no hot tearing crack and almost no micro-shrinkage can be achieved. The mechanism of grain refinement by combined effects of B, Na and Sr is yet to be understood, but it cannot be related to the distribution of micro-scale second phase. The highest ultimate tensile strength of the alloy achieved was about 178 MPa, nearly twice of that of the typical sterling silver alloy (about 90 MPa). This confirms advantages of the grain-refined alloy on jewelry application.